36-x=(13x-5)+(2x+9)

Simple and best practice solution for 36-x=(13x-5)+(2x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36-x=(13x-5)+(2x+9) equation:



36-x=(13x-5)+(2x+9)
We move all terms to the left:
36-x-((13x-5)+(2x+9))=0
We add all the numbers together, and all the variables
-1x-((13x-5)+(2x+9))+36=0
We calculate terms in parentheses: -((13x-5)+(2x+9)), so:
(13x-5)+(2x+9)
We get rid of parentheses
13x+2x-5+9
We add all the numbers together, and all the variables
15x+4
Back to the equation:
-(15x+4)
We get rid of parentheses
-1x-15x-4+36=0
We add all the numbers together, and all the variables
-16x+32=0
We move all terms containing x to the left, all other terms to the right
-16x=-32
x=-32/-16
x=+2

You can always share this solution

See similar equations:

| 13x+4=x?2 | | -6(6g+16)=12g | | 36-x=(13x-5)+(36-x) | | 6n-6+2=2 | | a-1/2-5(a-1)/8=3a+9/4 | | 2x+8-6=12 | |  2k+2=-13-3k  | | (5r-3)(r-8)=0 | | 7/2y-5=11 | | 2.5x+x=5x-6 | | 3x^2-6x+3=0 | | 2x+2+12-x=4x | | 11w-w-3w-2w=5 | | 7x+4=(x+3)+(8x-9) | | 6(x+8)-2(-15+4)=31 | | 7a/3+4=18 | | 5x+2=27+(3x-1) | | 5m+7=34 | | 2x+72=98 | | 12x+2(x+8)+6=8-(-4x+6) | | 4x-60=40 | | 86+6x-60+2x=50 | | X=0,y=2 | | 4x-16+14+6=62 | | 2x+3=24-x | | y²-y-6=0 | | 2x-3+2x-3=5x-12 | | 75=3(f-60) | | -9x=1-4-9 | | 5x=x+5/3x+7 |

Equations solver categories